I am having trouble understanding the derivation of the integral formula, most papers just assume the resistance to bending is:


I have found some derivation but they are missing a step, how is the bottom summation formula, $$E=-\frac{B}{b}\sum_{i=2}^N\cos(\theta_i) - Fb\sum_{i=1}^N \cos(\gamma_i)$$ transformed to the integral formula: $$ \frac{E}{k_BT}=\frac{\xi_T}{2}\int_0^L\left(\frac{d\vec{t}(s)}{ds}\right)^2ds - \frac{F}{k_BT}\int_0^L \cos(\gamma(s))ds$$

Where $\xi_T=B/k_BT$ and $\cos(\theta_i)=\vec{t}_i\cdot\vec{t}_{i+1}$, when $b \to 0$, $\ t_i=t(s)$ and $t_{i+1}=t(s+ds)$

The question might be answer in some paper, but I can't find it so if you now where I could look this up or you know how to do this. I would greatly appreciate it.


1 Answer 1


After some more searching I found a relevant paper that answers my relativity trivial question:

Milstein, J. N., & Meiners, J.-C. (2013). Worm-Like Chain (WLC) Model. Encyclopedia of Biophysics, 2757–2760. doi:10.1007/978-3-642-16712-6_502


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.